Handling storms at sea the five secrets of heavy weather sailing - Roth, Hal 1927- (Camden, Me. International Marine / McGraw-Hill, 2009)
A look at the ocean; Responding with onboard controls; Responding with off-boat controls; Planning, chartwork, hurricanes, and fear
Includes bibliographical references and index.
Keywords: Sailing; Heavy weather seamanship; Thuyền buồm; Đua thuyền